The Effectiveness of Website-Assisted Ethnomathematics-Based RME on Junior High School Students’ Understanding of Mathematics - Fikri, Darojatun; Hartono, Hartono; Arliani, Elly (Department of Mathematics Education, Faculty of Teacher Training and Education, Universitas Jambi, 2025)
This study examines the effectiveness of Realistic Mathematics Education, also supported by a website based on ethnomathematics, on the understanding of math concepts among junior high school students. The research method used in this study is quantitative research with a pre-experimental design, one-group pretest-posttest. The sample in the study was 29 students, which was taken from the 8th-grade students of a junior high school in Yogyakarta, picked through cluster random sampling. This study’s instruments were essay tests, which had been validated and proven reliable. The data from the research were analysed by descriptive and inferential statistics, where the inferential statistics included the Normality Shapiro-Wilk test and the One-Sample T-Test. The results indicated a significant improvement in students' understanding of math concepts after using RME through ethnomathematics-based website reach a significant change. This is evidenced by the posttest average value of 82.228, which is far more significant than the Minimum Mastery Criteria value of 75, and 79.31% of the students achieved and exceeded it. These results suggest that including local cultural contexts, batik motifs, and the Borobudur Temple structures in students’ learning process can enhance the students’ conceptual achievement level by strengthening the relationship with the learning process in their daily lives.